Benchmark of the Oxford Nanopore, EM-seq, and HumanMethylationEPIC BeadChip for the detection of the 5mC sites in cancer and normal samples - Deinichenko, Kseniia A.; Vynogradskaya, Valentina G.; Grebnev, Pavel A.; Mikova, Valeriya M.; Bobylev, Dmitriy O.; Shaymardanov, Abusaid M.; Ivashechkin, Alexey A.; Erokhina, Marina V.; Akinshina, Alexandra I.; Semyanihina, Anna V.; Mitrofanov, Sergey I.; Grammatikati, Konstantin S.; et al. (Frontiers in Epigenetics and Epigenomics, 2024)
Introduction: Whole-genome DNA methylation identification is crucial for profiling physiologically and clinically relevant epigenetic changes. Although there are multiple experimental methods, their accuracy, advantages, and disadvantages need to be investigated in their application to complex tissue objects. In this study, we performed a benchmark of 5mC detection with Oxford Nanopore and enzymatic methyl-sequencing (EM-seq) methods. Material and Methods: To this end, we profiled in a genome-wide manner 5mC sites in colorectal tumors and normal tissues for three patients and applied the HumanMethylationEPIC BeadChip as an additional control approach. We estimated the whole-genome scale of the methylation detection that each method yields. Results: Our investigation describes the sensitivity and specificity of each platform and the impact that sequencing coverage brings. Our analysis revealed the higher sensitivity and specificity of Nanopore sequencing over the EM-seq method. Moreover, Oxford Nanopore Technology (ONT) sequencing, followed by Megalodon methylation detection, demonstrates better quantitative agreement of the epigenetic signals between biological replicates. Furthermore, our analysis highlights that with 40× and above coverage, EM-seq slightly outperforms ONT and yields highly accurate detection of the 5mC signals (AuPR = 0.99178 and AuROC = 0.98161). Conclusion: The study was performed on colon cancer and adjacent normal tissue samples, placing our investigation close to the real application of methylation studies in oncology.